2018
DOI: 10.1093/infdis/jiy266
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Filovirus Infection of Rousettus aegyptiacus Bats in Zambia

Abstract: Bats are suspected to play important roles in the ecology of filoviruses, including ebolaviruses and marburgviruses. A cave-dwelling fruit bat, Rousettus aegyptiacus, has been shown to be a reservoir of marburgviruses. Using an enzyme-linked immunosorbent assay with the viral glycoprotein antigen, we detected immunoglobulin G antibodies specific to multiple filoviruses in 158 of 290 serum samples of R aegyptiacus bats captured in Zambia during the years 2014-2017. In particular, 43.8% of the bats were seroposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Recently, Towner et al demonstrated MARV transmission from inoculated to naïve Egyptian rousette bats [17], establishing Egyptian rousette bats as a natural reservoir of Marburgvirus (MARV and Ravn virus, RAVV). A seroprevalence of 20.5% was established in wild-caught Egyptian rousette bats from the Democratic Republic of the Congo [7]; 43.8% from Zambia [18] and 14.8% and 21.5% from juvenile and adult bats, respectively, captured in the Python Cave in Uganda [16]. In addition, the complete genome of Bombali virus (BOMV), a novel genera, was detected in the faeces of little free-tailed bats ( Chaerephon pumilus ) and Angolan free-tailed bats ( Mops condylurus ), demonstrating that bats, at a minimum, are part of the filovirus transmission cycle [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Towner et al demonstrated MARV transmission from inoculated to naïve Egyptian rousette bats [17], establishing Egyptian rousette bats as a natural reservoir of Marburgvirus (MARV and Ravn virus, RAVV). A seroprevalence of 20.5% was established in wild-caught Egyptian rousette bats from the Democratic Republic of the Congo [7]; 43.8% from Zambia [18] and 14.8% and 21.5% from juvenile and adult bats, respectively, captured in the Python Cave in Uganda [16]. In addition, the complete genome of Bombali virus (BOMV), a novel genera, was detected in the faeces of little free-tailed bats ( Chaerephon pumilus ) and Angolan free-tailed bats ( Mops condylurus ), demonstrating that bats, at a minimum, are part of the filovirus transmission cycle [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, over 80 distinct MARV genomic sequences and 21 virus isolates have been obtained from tissues of infected wild-caught ERBs, representing every major MARV strain found in MVD outbreaks since 1967, with the exception of the Angola strain 9 . In Gabon, South Africa and Zambia, MARV was detected in ERBs despite no known associated human MVD outbreaks in the country [16][17][18][19][20] . Here, through a combined multi-institutional effort, we report the presence of MARV, including an Angola-like MARV, in ERBs in West Africa.…”
mentioning
confidence: 97%
“…Extensive field studies in Uganda [12][13][14] , DRC 10 , Kenya 15 , South Africa 16 , Gabon 17,18 , and Zambia 19,20 , as well as experimental infection studies in captive bats in the United States 21,22 and South Africa 23,24 , have shown that the cave-dwelling Egyptian rousette bat (ERB; Rousettus aegyptiacus) is a primary natural reservoir of MARV. This discovery is consistent with the origins of MVD outbreaks that, when known, have been linked to caves or mines, with MARV most often having spilled over to miners who work underground in known ERB roosting sites, and occasionally to tourists who viewed ERBs too closely [25][26][27][28] .…”
mentioning
confidence: 99%
“…In addition, a number of novel FiVs have been discovered in bats in China and Africa which are divergent enough to be candidates for new species or even genera (11)(12)(13)(14)(15)(16). Particularly in China, reservoirs (17)(18)(19)(20)(21)(22). However, such serological data can be challenged as to interpretation, mainly due to unidentified cross-antigenicity between different FiV NPs.…”
mentioning
confidence: 99%